The impact of COVID-19 circuit breaker measures on the exercise behaviour of competitive athletes in Singapore - Sim, Regine Lee Ching (Nanyang Technological University, 2020)
Background: Competitive athletes faces an abrupt disruption from their regular training due to COVID-19 Circuit Breaker, causing severe reduction in the quality and quantity of their training.